The Effect of Emotional Intelligence and Cognitive Ability on the Performance of Private Higher Education Lecturers - Eva Solita Pasaribu; Benjamin Situmorang; Zainuddin Zainuddin; Panigoran Siburian (Budapest International Research and Critics University, 2022)
The success of private and public higher education organizations in implementing the Tridharma, namely teaching, research and service, is largely determined by the performance of lecturers as human resources who manage the Tridharma process. Therefore, the performance of lecturers must be managed properly in order to be successful and efficient in achieving educational goals, and to ensure an increase in the quality of higher education. To obtain optimal lecturer performance at a private university, it is necessary to pay attention to the factors of emotional intelligence and cognitive abilities. Lecturers who have controlled emotional intelligence and good cognitive abilities will have good performance. This study aims to determine the effect of emotional intelligence and cognitive abilities on lecturer performance. The number of samples set in this study were 146 lecturers as respondents. As an independent variable, namely emotional intelligence and cognitive ability and the dependent variable is the performance of the lecturer. For data collection is done by using a questionnaire with five answer choices. The sampling technique used is proportional random sampling. The instrument used was first tested on respondents outside the sample to get a valid and reliable instrument. The validity test uses the Product Moment correlation, while to test the reliability it uses the Alpha formula from Cronbac. Before testing the hypothesis, the analysis requirements test is calculated which includes: data normality test and regression linearity test. The results showed that the emotional intelligence variable had a direct positive effect on lecturer performance by 3.2%, and the cognitive ability variable had a direct positive effect on lecturer performance by 5.5%.